ANALYSIS OF TRANSLATION SHIFT IN A NOVEL (ENGLISH-INDONESIAN TRANSLATION) - Maria Gratia Ondok; Gunawan Tambunsaribu (Prodi Sastra Inggris UKI, 2020)
Abstract:This research aims to find out the class shift and structure shift in the simple sentences of Turtles All The Way Down novel by John Green (2018) and the translation into Bahasa Indonesia by Prisca Primasari (Penerbit Qanita, 2018). This research uses the theory of translation shift by Catford and equivalence by Nida. Catford divided translation shift into two, and they are level shift and category shift. Category shift is divided into four: structure shift, class shift, unit shift, and intrasystem shift. From those kinds of translation shifts, the writer chose two types of translation shifts: class shift and structure shift. According to Nida, there are two types of equivalence; they are formal equivalence and dynamic equivalence. After analyzing all data that has been collected by using those two theories which have been mentioned above, the writer finds out nine kinds of class shift which occur. They are pronoun to the noun, adverb to the adjective, the preposition to the verb, verb to an adverb, verb to pronoun, noun to adjective, adjective to the verb, the verb to the adjective, and adverb to verb. Other than that, for structure shift, the writer finds out that word order changes, extra word added, and removal of some sentence elements in the simple sentences. The structure shift and class shift done by the translator show that each simple sentence with structure shift and class shift in the novel has one of two types of equivalence based on Nida’s theory.Keyword: Translation, class shift, structure shift, translation shift, equivalence